Selective hydrogenation of p-chloronitrobenzene over an Fe promoted Pt/AC catalyst. Issue 46 (5th June 2017) - Chen, Hu; He, Daiping; He, Qingqing; Jiang, Ping; Zhou, Gongbing; Fu, Wensheng
Abstract : Selective production of p -chloroaniline from p -chloronitrobenzene without any further hydrogenation products was found feasible by catalytic hydrogenation over the Pt–Fe/AC catalyst. Abstract : Activated carbon supported Pt (Pt/AC) and Fe modified Pt (Pt–Fe/AC) catalysts have been investigated for selective hydrogenation of p -chloronitrobenzene to p -chloroaniline. It was found that the incorporation of an appropriate amount of Fe (4 wt%) resulted in a remarkable increase in activity and selectivity to p -chloroaniline, and the catalytic hydrodechlorination over the catalyst was fully suppressed at complete conversion of p -chloronitrobenzene. X-ray photoelectron spectroscopy (XPS) revealed the electron transfer from Pt nanoparticles to Fe2 O3, leading to the electron-deficient state of the Pt nanoparticles in the present catalyst, which is responsible for improved performance of the Pt–Fe/AC catalyst for p -chloronitrobenzene hydrogenation to p -chloroaniline.